Analysis And Design School Website Profiles Sekolah Menengah Kejuruan Negeri 2 Kabupaten Pacitan - Kuswati, Endang (Seruni - Seminar Riset Unggulan Nasional Inoformatika dan Komputer, 2012)
Information technology is an important part in the development of education. Internet is a place where students and teachers can access the knowledge and information. Informatics technology widely applied to the delivery and management of information because the effectiveness and efficiency are shown to speed up performance, and ultimately will improve the quality of schools. SMK Negeri 2 Donorojo Pacitan in the delivery of information written on the bulletin board, brochures and banners. SMK Negeri 2 Donorojo not yet have a website as a means of delivering information. This study aims to analyze and design the school profile website. With the analysis and design is expected to be able to answer the difficulties often faced by employees and students as well as the parties involved in education to find out information SMK Negeri 2 Donorojo. Data collection methods used in this study include: problem identification, data collection and information, study library, survay method. The results of this study can facilitate all stakeholders to access information SMK N 2 Donorojo. Keyword : School Profile Website